Optimizing the magnetic separation of strontium ion using modified zeolite with nano iron particles - Tamer Shubair; Atsushi Tahara; Shahjalal Khandaker (Case Studies in Chemical and Environmental Engineering, 2022)
This work aims at investigating the adsorption behavior of a magnetic adsorbent (zeolite/Fe0) consisting of zeolite and nano iron particles toward strontium (Sr) by batch kinetic and equilibrium studies. In the kinetic data demonstration, pseudo-first-order, pseudo-second-order, Elovich and diffusion-based models were employed. The equilibrium data were analyzed using Langmuir, Freundlich, Dubinin–Radushkevich, Redlich–Peterson and Temkin isotherm models. Statistical analyses were also used to optimize the regression goodness and assess the model sensitive parameters that can affect the Sr removal process reliability. The adsorption kinetic data were found to be well fitted with the pseudo-second-order model, which showed that the process was quite rapid. The Langmuir adsorption isotherm was the best model to describe the adsorption process, indicating that the Sr removal mechanism was monolayer chemisorption involving ion exchange. It was confirmed that the zeolite/Fe0 is an appropriate adsorbent material for the removal of Sr from contaminated water.